2000
DOI: 10.1046/j.1523-1747.2000.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythroplasia of Queyrat: Coinfection with Cutaneous Carcinogenic Human Papillomavirus Type 8 and Genital Papillomaviruses in a Carcinoma In Situ

Abstract: Erythroplasia of Queyrat is a carcinoma in situ that mainly occurs on the glans penis, the prepuce, or the urethral meatus of elderly males. Up to 30% progress to squamous cell carcinoma. The cause of erythroplasia of Queyrat is largely unknown. Human papillomavirus type 16 DNA has previously been detected only in very few distinctly characterized patients. We have investigated 12 paraffin-embedded biopsies from eight patients with penile erythroplasia of Queyrat and control biopsies of inflammatory penile les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(105 citation statements)
references
References 32 publications
4
98
2
1
Order By: Relevance
“…For HIV-positive patients, the number of CD4 cells per microliter, the HIV type 1 RNA load in plasma (Cobas Amplicor HIV-1 Monitor 1.5; Roche, Mannheim, Germany), and Centers for Disease Control and Prevention stage (8) were determined. DNA isolation from cervical scrapes (QIAamp-DNA Mini-Kit; Qiagen, Hilden, Germany), ␤-globin gene PCR (2), HPV screening-PCR (45), and HPV typing (22) were performed as previously described. Sample characteristics and HPV DNA prevalence data are given in Table 1.…”
mentioning
confidence: 99%
“…For HIV-positive patients, the number of CD4 cells per microliter, the HIV type 1 RNA load in plasma (Cobas Amplicor HIV-1 Monitor 1.5; Roche, Mannheim, Germany), and Centers for Disease Control and Prevention stage (8) were determined. DNA isolation from cervical scrapes (QIAamp-DNA Mini-Kit; Qiagen, Hilden, Germany), ␤-globin gene PCR (2), HPV screening-PCR (45), and HPV typing (22) were performed as previously described. Sample characteristics and HPV DNA prevalence data are given in Table 1.…”
mentioning
confidence: 99%
“…In EQ, a strong association with HPV 16 was reported by previous studies and coinfection by HPV type 8 with types 16, 39 and 51 also have been identified. However, HPV type 8 was not detected in cervical or vulvar precancerous and cancerous lesions and in BD lesions 5 . Additionally, HPV DNA was found in 31% of extragenital Bowen's disease but no individual HPV type predominated in BD 6 .…”
Section: Discussionmentioning
confidence: 88%
“…In EQ, a strong association with HPV 16 was reported by previous studies and coinfection by HPV type 8 with types 16, 39 and 51 also have been identified. 10 Treatment options include surgical excision, topical imiquimod, 5-fluorouracil. Carbondioxide laser and radiation therapy have also been useful in treatment of EQ.…”
Section: Discussionmentioning
confidence: 99%